Abuse of Authority in Utilizing Village Funds as an Effort to Win the 2024 Presidential Election in Indonesia Seen from Qualitative Evidence - Aslan Noor; Guntur Atur Parulian; Fachrully Pratama; Agung Dwi Pranyoto; Raineka Faturani Quran (Dinasti Research, 2024)
This research aims to examine the abuse of authority in the use of village funds as a political strategy to win the 2024 Presidential Election (Pilpres) in Indonesia. Through a qualitative approach, this research explores how village funds, which should be used for community development and welfare, are misused by certain individuals for political purposes. Data analysis was carried out using the triangulation method to ensure the validity and reliability of the findings. The research results show that misuse of Village Funds for political interests, especially in the context of the 2024 Presidential Election, is a practice that damages the integrity of democracy and the welfare of village communities. It was found that the politicization of Village Funds, active or passive support from village heads for certain candidates, distribution of basic necessities with political motives, and direction to elect candidates with the threat of stopping Social Assistance are forms of abuse of power that violate the principles of democracy and human rights. The impacts include losses in development and public services, as well as creating distrust of village government and the political system. To overcome this, firm steps are needed such as strict supervision, fair law enforcement, political education for the community, and policy reform to increase transparency and accountability in the use of Village Funds.